DuqueXII: a robotics-based approach for mitigating domestic accidents in early childhood (2025)
DuqueXII is a robot designed to prevent domestic accidents in early childhood through advanced sensors, computer vision and artificial intelligence. It features a PTZ camera for real-time inference and a sensor network to monitor environmental conditions like proximity, light, temperature, sound and flame presence. Its design allows 360-degree movement and head articulation, with RGB LEDs indicating states and alerts. Using a hybrid ROS-based architecture, DuqueXII is optimized for real-time performance. This work details its design, development and validation in controlled environments, demonstrating its effectiveness in ensuring child safety with applications in homes and childcare settings.